Keterlambatan Membaca dan Fokus Siswa Kelas 3 SD : Analisis dan Strategi Pembelajaran Efektif - Aisyah Fadhilah; Dessy Mutia; Adrias Adrias; Fadila Suciana (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Reading delays and low learning focus in grade 3 elementary school students are significant challenges in primary education. This study aims to analyze the factors that cause reading delay and decreased learning focus in grade 3 elementary school students, as well as explore effective learning strategies to overcome them. The method used is a literature study by reviewing various related scientific sources. The results of the analysis show that internal factors such as low reading interest and lack of motivation, as well as external factors such as lack of family support and a less conducive learning environment, contribute to reading delays and decreased study focus. Learning strategies involving phonic methods, multisensory approaches, and the use of educational technology have proven to be effective in improving students' reading and focus skills. The implications of these findings emphasize the importance of the role of teachers and parents in creating a supportive learning environment and implementing appropriate learning methods to address reading delays and improve students' focus on learning.